UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN THINK PAIR AND SHARE (TPS) - Kristiana Purwantari (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purpose of this study was to describe the implementation process of learning mathematics through the learning model And Think Pair Share (TPS) in order to increase student motivation and learning achievement of class VII F SMP N 2 Greetings. The subjects in this study were students of class VII F SMP N 2 Regards, while the object of the study was motivation and achievement in the implementation of learning mathematics using learning models And Think Pair Share (TPS).Data collection techniques in this study performed using the observation sheet, sheet motivation questionnaire, and learning achievement tests. Instrument research using observation sheets, questionnaire motivation, and test.Data analysis techniques for observation sheet is done by calculating a percentage score for each indicator while learning mathematics achievement is done by calculating the average value of the percentage of students who meet the grade criteria for completeness Minimal. The results showed that after learning model applied And Think Pair Share (TPS) and the motivation to learn mathematics achievement increased. This can be shown by an increase in the average yield percentage of student motivation based on the observation sheet. Based on the observation sheet for each cycle is the first cycle of students at 62.50%, for the second cycle of 72.22%. While the average value of learning mathematics achievement of students increased from an average initial value of 72.12 into a 75.26 in the first cycle and the second cycle becomes 80.32. Given the learning model And Think Pair Share (TPS) to further encourage student motivation and also can improve students' mathematics learning achievement, the school is expected to apply the learning model.